PENINGKATAN KEMAMPUAN BERMUSIKALISASI PUISI MELALUI TEKNIK PEMODELAN PADA SISWA KELAS X - Heryanti Heryanti; Mulyanto Widodo (Universitas Lampung, 2017)
This study aimed to describe the increase in the ability of musical poetry in class X State Senior High School 1 Pringsewu the school year 2016/2017 used modeling techniques. This study used a Class Action Research. Improved processes can be seen from the role and activities of teachers and students who have increased significantly in the implementation of learning. Improved learning outcomes can be seen from the increase in the value end of the poem bermusikalisasi pratindakan students from stage to stage of the second cycle. Obtaining the average value of the final musical poetry pratindakan students on stage, which is 67.5. In the first cycle, increased to 73.8. Then, in the second cycle the average value of student learning outcomes back end has increased to 82.89. The amount of increase in the average value of final pre action musical poetry until the second cycle of 15.39.Penelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan musikalisasi puisi pada siswa kelas X SMA Negeri 1 Pringsewu tahun pelajaran 2016/2017 dengan menggunakan teknik pemodelan. Peningkatan proses dapat dilihat dari peran serta aktivitas guru maupun siswa yang mengalami peningkatan secara signifikan dalam pelaksanaan pembelajaran. Peningkatan hasil belajar dapat dilihat dari peningkatan nilai akhir bermusikalisasi puisi siswa mulai dari tahap pratindakan sampai tahap siklus II. Perolehan rata-rata nilai akhir musikalisasi puisi siswa pada saat tahap pratindakan, yaitu 67,5. Pada siklus I, mengalami peningkatan menjadi 73,8. Kemudian, pada siklus II rata-rata nilai akhir hasil belajar siswa kembali mengalami peningkatan menjadi 82,89. Jumlah peningkatan rata-rata nilai ahkir musikalisasi puisi dari pratindakan sampai siklus II sebesar 15,39.Kata kunci: peningkatan, kemampuan, musikalisasi puisi, teknik pemodelan.